2016
DOI: 10.1038/cddis.2015.397
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulates odontoblast differentiation by suppressing NF-κB activation in an inflammatory environment

Abstract: Odontoblasts are derived from dental papilla mesenchymal cells and have an important role in defense against bacterial infection, whereas autophagy can recycle long-lived proteins and damaged organelles to sustain cellular homeostasis. Thus, this study explores the role of autophagy in odontoblast differentiation with lipopolysaccharide (LPS) stimulation in vitro and the colocalization of p-NF-κB and LC3 in caries teeth. The odontoblasts differentiation was enhanced through LPS stimulation, and this outcome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…Recent studies have discovered that inflammatory cytokine could attenuate the odontoblastic differentiation of dental stem cells [35]. Furthermore, Pei et al reported that autophagy induced by inflammatory environment is critical in regulating odontoblastic differentiation [36]. More highly reserved ATGs have been identified in regulating the odontoblastic differentiation of stem cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have discovered that inflammatory cytokine could attenuate the odontoblastic differentiation of dental stem cells [35]. Furthermore, Pei et al reported that autophagy induced by inflammatory environment is critical in regulating odontoblastic differentiation [36]. More highly reserved ATGs have been identified in regulating the odontoblastic differentiation of stem cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the work thus far has focused on the role of autophagy in osteoblastic differentiation. One study reported that autophagy is involved in the osteogenic differentiation of odontoblasts [131] and human osteoblast associated with the titanium-based dental implants [132]. In mesenchymal stem cells (MSCs), autophagy is induced by forkhead box O3 (FOXO3) to reduce ROS resulting from the increased mitochondrial respiration that occurs during osteoblast differentiation [133] and may regulate osteogenic differentiation via AMPK/Akt/mTOR signaling [134].…”
Section: Possible Mechanisms By Which Hmgb1 Promotes Cardiovascular Cmentioning
confidence: 99%
“…Accumulating evidence shows that LPS causes inflammatory reactions in DPCs and promotes translocation of p65 from the cytoplasm to the nucleus (Pei et al 2016). Accumulating evidence shows that LPS causes inflammatory reactions in DPCs and promotes translocation of p65 from the cytoplasm to the nucleus (Pei et al 2016).…”
Section: Discussionmentioning
confidence: 99%